3D In Situ ToF‐SIMS Imaging of Perovskite Films under Controlled Humidity Environmental Conditions. Issue 2 (27th December 2016) - Lin, Wei‐Chun; Chang, Hsun‐Yun; Abbasi, Kevin; Shyue, Jing‐Jong; Burda, Clemens
Abstract : Since CH3 NH3 PbI3 perovskites are discovered as a viable active material for next‐generation photovoltaic devices, their instability in humid environments is a constant challenge. Therefore, understanding the exact spatially resolved degradation process is a crucial need before being able to improve the stability and durability of these exceptional materials. In this work, it is demonstrated that the CH3 NH3 PbI3 perovskite will eventually degrade irreversibly at high humidity through a slow leaching and vaporization process of CH3 NH2 . Deuterium oxide (D2 O) is used as a humidity source instead of H2 O to distinguish the exogenous water diffusing into the perovskite from moisture embedded during sample fabrication. The degradation process of CH3 NH3 PbI3 perovskite is examined in situ by using time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS) and an argon ion cluster beam for layer‐by‐layer in situ sputtering and then compared to their corresponding solar cell performances. 3D images are constructed from the layer‐by‐layer spatially resolved elemental distribution analysis and the D2 O moisture penetration through the sample. It is observed that the H/D exchange on the organic methylammonium ion is the first indication for moisture uptake in a given volume element. The intermediate products of interaction with moisture are also analyzed by ToF‐SIMS and X‐ray photoelectron spectroscopy. The initial products of this deuterium exchange reaction are CH3 NH2 D, CH3 NHD2, and CH3 ND3 . In the following, the D2 O molecule stepwise replaces the methylammonium, which leads to evaporation of the organic molecules and eventually to erosion of the perovskite along with drastic changes in morphology, crystallography, and photovoltaic performance. Abstract : Time‐of‐flight secondary ion mass spectrometry is used to investigate the degradation of perovskite films in controlled humidity condition. Deuterium oxide (D2 O) is used as humidity instead of H2 O to distinguish the exogenous water diffusing into the perovskite from moisture embedded during sample fabrication. Depth profiling and 3D reconstructive imaging are demonstrated to explain the decomposition process.